Electricity sector transition in the national electricity market of Australia: Managing reliability and security in an energy-only market - Billimoria, F; Poudineh, R (Oxford Institute for Energy Studies, 2018)
Australia’s National Electricity Market is an important global test case of the impacts of electricity sector transition in a large-scale liberalized energy-only market. The integration of variable and distributed energy resources has provided opportunities for clean, low-cost generation, but has also challenged existing market frameworks and resulted in a debate about the necessity for new designs. The market’s delayed and insufficient response to disorderly retirement and the need for certain system services have resulted in government and system operator intervention to bridge the gap. There are difficulties in securing timely new investment under policy uncertainty and integrated capital models. Furthermore, contributions to system services that were previously provided as a consequence of energy provision are not inherently provided by many new-generation technologies. A range of solutions have been proposed to address these challenges, although none to date have harnessed the potential of comprehensive alignment between operational requirements and economic signals. For example, the government’s flagship National Energy Guarantee, while providing a new framework for emissions intensity and reliability, did not address the ‘missing markets’ in energy security. Measures such as forward markets may provide hedging options, but are limited to energy. Centralized commitment could provide operating robustness, but might not be able to provide sufficient transparency of the various electricity value streams, as the experience of international markets shows. Furthermore, while reliability has taken centre stage in the policy discourse, system security is as important in managing a large-scale complex grid with a significant share of asynchronous generation. We argue that an efficient and transparent real-time energy market must reflect the comprehensive operational requirements of electricity dispatch. This necessitates an extension of energy-only design to an ‘energy+services’ model in which efficient price signals are provided for the ‘missing products’ necessary for operational security. Clear service specifications provide transparent signals that enable clear price discovery and facilitate competition from new providers and technologies.